DETERMINASI PERILAKU MUZZAKI DALAM MEMBAYAR ZAKAT PROFESI - Syawal Harianto; Erni Nonita Qia; Teuku Fakhrial Dani (Politeknik Negeri Medan, 2020)
This study aims to determine the influence of attitude, subjective norm, PBC and religiosity on behavior in paying zakah with intention as mediating variable. Sample in this study is the teaching staff in Lhokseumawe that involved 150 respondents who answered 36-item questionnaire statements. This study used a likert scale measurement and sampling technique with Accidental sampling. Then used path analysis method with SPSS version 18 for Windows. The results of this study: On simultaneous test result, shows that attitude, subjective norm, PBC, religiosity and intention have simultaneously and significant influence on behavior variable. On partial test result, shows that attitude has direct effect to behavior variable in paying zakah profession. Subjective norm has not significant effect to intention and behavior variabel. So, subjective norm should be excluded from this research. Then, PBC has indirect effect to behavior variabel with intention as mediation. Finally, religiosity variable has dominant direct effect than indirect effect on behavior with intention as mediation.